Unravelling the self-image of the Indian bomb lobby - Vanaik, Achin (2004)
The sociology of the Indian bomb lobby, the intelligentsia and middle class is intimately and unavoidably connected to the wider sociology of change in India. What is suggested here is that it is these very processes that are central to explaining why Indian went openly nuclear and why elite nationalism continues to favour the possession and development of a nuclear weapons system. The decisive factor in the transition of India from ambiguity to declared nuclear status was played by a coterie within the decision-making circle. It then took along with it an already enthusiastic pro-bomb following, as well as a taken-by-surprise but easily adjusting and suddenly enthusiastic remaining part of the newly created bomb lobby. - Reproduced.
Keywords: Middle class